2011
DOI: 10.1118/1.3612365
|View full text |Cite
|
Sign up to set email alerts
|

SU‐E‐T‐411: Validation of Plan Dose Perturbation Software for Use in Patient Specific IMRT Quality Assurance

Abstract: Purpose: Patient‐specific IMRT quality assurance typically compares measured and calculated dose distributions in‐phantom. The clinical importance of disagreement between measured and calculated dose is often difficult to interpret. Recently, software has been developed (3DVH Sun Nuclear, Florida USA) that calculates the “delivered” dose distributions in patients by perturbing the calculated dose using errors detected in planar dose measurements. The aim of this work was to validate the accuracy of 3DVH versus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…As a result, new approaches based on 3D dose reconstruction and DVH metrics have recently been developed and tested. [9][10][11] Although it has been suggested 8 that false positive and false negative can result from a per-beam gamma analysis, this hypothesis has not yet been clinically demonstrated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, new approaches based on 3D dose reconstruction and DVH metrics have recently been developed and tested. [9][10][11] Although it has been suggested 8 that false positive and false negative can result from a per-beam gamma analysis, this hypothesis has not yet been clinically demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…First, we designed some in-phantom tests to elucidate the capabilities of new software based on DVH metrics and to highlight the flaws that can lead to false positives and false negatives in the conventional approach and to see if they were picked up in the 3DVH software. For the present study, real errors were created and delivered and they were measured with a commercial diode array; in contrast with previous studies 9,11 where errors were simulated and were quantified with an ideal planar detector. Second, we analyzed real patient verifications to highlight the information a DVH metric can typically provide compared to that of a 2D analysis and to see if differences could be related to gamma passing rates.…”
Section: Introductionmentioning
confidence: 99%
“…In the process of validation of the 3DVH software (6,8,9,(15)(16)(17)(18)(19), other QA tools have also been used, including for D 95 of PTV 59. 4 and mean larynx dose, respectively.…”
Section: Design Of the Studymentioning
confidence: 99%
“…Therefore, to predict clinically relevant patient dose errors, IMRT QA should include the evaluation of patient anatomy based metrics directly related to the clinical impact of the dose error. As a result, new approaches based on three-dimensional (3D) dose reconstruction and dose volume histogram (DVH) metrics have recently emerged and been tested (8,9). …”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown the validity of 3DVH (9,10,12,14,15) . Zhen et al (12) used 24 error‐free IMRT plans and introduced four types of errors to create 96 plans with errors.…”
Section: Introductionmentioning
confidence: 99%